Impact and seasonality of human rhinovirus infection in hospitalized patients for two consecutive years - Jaqueline Leotte; Hygor Trombetta; Heloisa Z. Faggion; Bernardo M. Almeida; Meri B. Nogueira; Luine R. Vidal; Sonia M. Raboni (Elsevier, 2017)
Objectives: To report epidemiological features, clinical characteristics, and outcomes of human rhinovirus (HRV) infections in comparison with other community acquired respiratory virus (CRV) infections in patients hospitalized for two consecutive years. Methods: This was a cross-sectional study. Clinical, epidemiological, and laboratory data of patients hospitalized with acute respiratory syndrome in a tertiary care hospital from 2012 to 2013 were reviewed. Results: HRV was the most common CRV observed (36%, 162/444) and was present in the majority of viral co-detections (69%, 88/128), mainly in association with human enterovirus (45%). Most HRV-infected patients were younger than 2 years (57%). Overall, patients infected with HRV had a lower frequency of severe acute respiratory infection than those infected with other CRVs (60% and 84%, respectively, p = 0.006), but had more comorbidities (40% and 27%, respectively; p = 0.043). However, in the adjusted analysis this association was not significant. The mortality rate within the HRV group was 3%. Detection of HRV was more prevalent during autumn and winter, with a moderately negative correlation between viral infection frequency and temperature (r = −0.636, p < 0.001) but no correlation with rainfall (r = −0.036, p = 0.866). Conclusion: HRV is usually detected in hospitalized children with respiratory infections and is often present in viral co-detections. Comorbidities are closely associated with HRV infections. These infections show seasonal variation, with predominance during colder seasons. Resumo: Objetivos: Relatar as características epidemiológicas, as características clínicas e os resultados das infecções por rinovírus humano (RVH) em comparação a outras infecções por vírus respiratórios adquiridos na comunidade (VRCs) em pacientes internados por dois anos consecutivos. Métodos: Este foi um estudo transversal. Foram revisados os dados clínicos, epidemiológicos e laboratoriais de pacientes internados com síndrome respiratória aguda em um hospital terciário de 2012 a 2013. Resultados: O RVH foi o VRC mais comum observado (36%, 162/444) e esteve presente na maior parte das codetecções virais (69%, 88/128), principalmente em associação ao enterovírus humano (45%). A maioria dos pacientes infectados por RVH possuía menos de 2 anos (57%). De modo geral, os pacientes com RVH apresentaram uma menor frequência de infecção respiratória aguda grave que os pacientes infectados por outros VRCs (60% e 84%, respectivamente, p = 0,006), porém mais comorbidades (40% e 27%, respectivamente; p = 0,043). Contudo, em uma análise ajustada, essa associação não foi significativa. A taxa de mortalidade no grupo RVH foi 3%. A detecção de RVH foi mais prevalente durante o outono e inverno, com uma correlação negativa moderada entre a frequência de infecção viral e a temperatura (r = -0,636, p < 0,001), porém nenhuma correlação com a precipitação (r = -0,036, p = 0,866). Conclusão: O RVH é normalmente detectado em crianças internadas com infecções respiratórias e normalmente está presente em codetecções virais. As comorbidades estão estreitamente associadas a infecções por RVH. Essas infecções mostram variação sazonal, com predominância durante as estações mais frias. Keywords: Human rhinovirus, Acute respiratory infections, Respiratory virus, Palavras-chave: Rinovírus humano, Infecções respiratórias agudas, Vírus respiratório